2021
DOI: 10.1002/pssr.202100254
|View full text |Cite
|
Sign up to set email alerts
|

2D Amorphous CoO Incorporated g‐C3N4 Nanotubes for Improved Photocatalytic Performance

Abstract: Hydrogen, as a clean fuel, has been considered as a promising alternative for traditional fossil fuels in the future. [1] The photocatalysis hydrogen evolution is identified as one of pollution-free methods to produce hydrogen on a large scale. [2][3][4] Since photo-induced water splitting on TiO 2 electrodes was discovered, great efforts have been made to develop catalysts for photocatalytic water splitting. [5,6] Up to date, various nanomaterials have been used as photocatalysts for the sunlightdriven H 2 ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…To detect the active species, an appropriate amount of capture agents listed as isopropyl alcohol (IPA) capturing hydroxyl radicals (·OH), benzoquinone (BQ) capturing superoxide radical ( · O 2 ), ethanol (EA) capturing VB‐holes, along with one control group without any scavengers, were carried out in the scavenger experiments of RhB degradation (Figure 7d). [ 43 ] As obviously seen, the decomposition of RhB is greatly hampered by the addition of BQ, indicating · O 2 radicals play a major role in photocatalytic reaction. Whereas, the degradation efficiency is hardly affected after the addition of IPA, demonstrating that the ·OH is not the main active species.…”
Section: Resultsmentioning
confidence: 99%
“…To detect the active species, an appropriate amount of capture agents listed as isopropyl alcohol (IPA) capturing hydroxyl radicals (·OH), benzoquinone (BQ) capturing superoxide radical ( · O 2 ), ethanol (EA) capturing VB‐holes, along with one control group without any scavengers, were carried out in the scavenger experiments of RhB degradation (Figure 7d). [ 43 ] As obviously seen, the decomposition of RhB is greatly hampered by the addition of BQ, indicating · O 2 radicals play a major role in photocatalytic reaction. Whereas, the degradation efficiency is hardly affected after the addition of IPA, demonstrating that the ·OH is not the main active species.…”
Section: Resultsmentioning
confidence: 99%
“…With this method, they further fabricated the 2D amorphous CoO incorporated g-C 3 N 4 nanotubes for improved photocatalytic water splitting (Fig 26d). [75]…”
Section: Photocatalytic Performance Of Other 2d Amorphous Materialsmentioning
confidence: 99%
“…The 2D/2D CN/a-ZnO heterojunction has abundant defects and Zn-N covalent bonding, large size, and perfect disordered interface, which can extend the light absorption range, increase the number of reaction sites, enhance the loading of the separation of the current, and promote charge transfer. Wang et al [15] investigated the incorporation of 2D amorphous CoO into g-C 3 N 4 nanotubes to improve the photocatalytic performance by CoO aggregation and thermally induced oxidation, and the results showed that the synthesized 2D/2D CN/a-CoO heterojunction significantly improved the degradation of rhodamine B, achieving an efficient space charge separation through Co-N bonds. Khatoon et al [16] studied the influence of Ni-doped ZnO on optical properties and magnetic properties by solvothermal synthesis method.…”
Section: Introductionmentioning
confidence: 99%